Evaluation of post‐colostrum ingestion changes in the protein composition of peripheral blood of newborn piglets: A pilot study. (10th December 2022) - Ito, Ken R.; Kawasaki, Kiyonori; Miura, Hiroto; Tsukahara, Takamitsu; Inoue, Ryo
Abstract: Putatively, colostral proteins are partly absorbed and transferred to blood circulation in newborn piglets, which suggests that colostrum ingestion alters the protein composition of their blood. Here, we conducted a pilot study to estimate the changes in the protein composition of piglet blood. Plasma collected from piglets pre‐ and post‐ingestion of colostrum (PreC and PostC) was analyzed by shotgun proteomics. Proteins in colostrum were also analyzed. We identified 393 and 427 proteins in PreC and PostC plasma, respectively, and 596 colostral proteins. Whereas 202 unique proteins were identified in PostC, PreC and PostC commonly shared 225 proteins. By contrast, when compared with PreC, 54 proteins in PostC had their emPAI values increased >2‐fold. Notably, using plasma samples collected from a separate experiment, the concentrations of growth differentiation factor 8 and haptoglobin were higher in PostC than in PreC, which was validated by ELISA. Approximately 60% of the uniquely identified or highly concentrated proteins in PostC were also found in colostrum, which were likely, at least partly, transferred from colostrum. The present study demonstrated that the protein composition of plasma of newborn piglets drastically changed post‐colostrum ingestion, partly due to transfer of colostral proteins.